Rahner’s Theology of the Priesthood and the Development of Doctrine - Lennan, Richard (Philosophy & theology, 2000)
This paper focuses on Karl Rahner’s understanding of the relationship between history and the church’s doctrine. It locates doctrine within Rahner’s view of the church as the sacrament of Jesus Christ in history and the development of doctrine as a response to issues raised by the church’s historical existence. Rahner’s theology of the priesthood is used as a concrete example of his understanding of doctrine and its development. The paper explores also the continuing value of Rahner’s ideas for the contemporary church.